2018
DOI: 10.1144/jgs2018-035
|View full text |Cite
|
Sign up to set email alerts
|

New 40 Ar/ 39 Ar dating of the Antrim Plateau Volcanics, Australia: clarifying an age for the eruptive phase of the Kalkarindji continental flood basalt province

Abstract: New 40Ar/39Ar dating of the Antrim Plateau Volcanics, Australia: clarifying an age for the eruptive phase of the Kalkarindji continental flood basalt province. Journal of the Geological Society, 175(6) pp. 974-985. For guidance on citations see FAQs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
2
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…While all the calcifying groups display the 'Lilliput Effect' in the aftermath of the Sinsk Event, both phosphatic linguliformean brachiopods and siliceous sponges manifest the opposite 'Brobdingnag Effect' -the within-species size increase of newly originated species 41 . The latter part of the Botoman-Toyonian extinction was coeval with emplacement of the Kalkarindji Large Igneous Province at 508-498 Ma 42 . This event, although potentially detrimental to the latest early Cambrian reef biota, post-dated the major animal size changes recorded here which occurred before 510 Ma.…”
Section: Discussionmentioning
confidence: 98%
“…While all the calcifying groups display the 'Lilliput Effect' in the aftermath of the Sinsk Event, both phosphatic linguliformean brachiopods and siliceous sponges manifest the opposite 'Brobdingnag Effect' -the within-species size increase of newly originated species 41 . The latter part of the Botoman-Toyonian extinction was coeval with emplacement of the Kalkarindji Large Igneous Province at 508-498 Ma 42 . This event, although potentially detrimental to the latest early Cambrian reef biota, post-dated the major animal size changes recorded here which occurred before 510 Ma.…”
Section: Discussionmentioning
confidence: 98%
“…This homogeneity was corroborated further by Evins et al (2009) who demonstrated the Table Hill Volcanics of southern WA to be near identical in their geochemistry and age. Further dating of associated intrusives (Macdonald et al, 2005;Jourdan et al, 2014;) and extrusives (Marshall et al, 2018) point toward a complex, extended magmatic history, beginning with intrusion into the Australian cratonic basement around 512 Ma, with final eruption of the APV occurring between 509 -498 Ma (Marshall et al, 2018). Magmatism is likely to have been driven by decompressional partial melting of an already warmed source material (due to edge-driven convection around the stable cratonic roots of the North Australian Craton) caused in part by the torsional stresses applied by the rapid rotation of the Gondwanan continent in the early Phanerozoic .…”
Section: Age Of Magmatismmentioning
confidence: 99%
“…Dates for the Kalkarindji range from c. 510 -500 Ma ( Fig. 4; Marshall et al, 2018), and so indicate that the Kalkarindji is too young to have been an instigating factor in driving the BTE, which culminated in the Toyonian at ~512 Ma (Brasier, 1996;Zhuravlev and Wood, 1996;Ogg et al, 2016).…”
Section: Biotic Instabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Following the BTE, dominant trilobite faunas from Laurentia and Gondwana were replaced at the Series 2-Miaolingian (previously known as the Cambrian Series 3; see the Subcommission on Cambrian Stratigraphy) boundary (Montañez et al, 2000;Zhu et al, 2006). These events have been speculatively linked to the emplacement of the Kalkarindji continental flood basalt province (CFBP) (Glass & Phillips, 2006;Jourdan et al, 2014), which erupted onto the Gondwanan conti nent in the mid-Cambrian, making this the oldest LIP in the Phanerozoic (Marshall et al, 2018;. Kalkarindji magmatism appears in apparent synchrony with disruption to the Cambrian carbon cycle, recorded as a large negative carbon isotope excursion (the Redlichiid-Olenellid Extinction Carbon Isotope Excursion; ROECE) at the Series 2-Miaolingian boundary (Montañez et al, 2000;Zhu et al, 2006;Faggetter et al, 2016Faggetter et al, , 2017Chang et al, 2017;Ren et al, 2018).…”
Section: Introductionmentioning
confidence: 99%